Caring for Children Born Small for Gestational Age - Zabransky, Siegfried; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
Care for Children Born Small for Gestational Age is a comprehensive handbook that serves to synthesize the extensive recent literature in the area to provide a practical resource aimed at a wide range of healthcare professionals, including obstetricians, midwives, neonatologists, and primary care physicians. This comprehensive handbook includes an in-depth survey of the prevention, diagnosis, treatment and long-term monitoring of children born small for gestational age, as well as related conditions such as intrauterine growth restriction, metabolic syndrome and type 2 diabetes. Additionally, the short and long-term psychiatric and social consequences of this condition are addressed.
Fetal Development -- Intrauterine aspects -- Maternal nutrition -- Prenatal care, surveillance, and risk assessment -- Birthweight percentiles: an international comparison -- Fetal growth restriction: definitions, causes, and epidemiology -- Obstetric aspects -- Placental function in intrauterine growth restriction -- Placental function: predicting impairment -- The role of genetic and epigenetics in growth restriction -- Fetal programming -- Premature infants -- Term newborns -- Endocrine regulation of fetal growth -- Growth hormone treatment -- Renal function -- Pancreatic development -- Metabolic syndrome -- Cardiovascular risks and diseases -- Ophthalmological findings and visual function disorders -- Auditory function disorders -- Neurological, neurocognitive and behavioural aspects -- Prevention and long term care -- Considerations for future research.
Keywords: Medicine; Obstetrics; Maternal and infant welfare; Endocrinology; Metabolic diseases; Pediatrics; Medicine & Public Health; Pediatrics; Obstetrics/Perinatology.; Maternal and Child Health; Health Promotion and Disease Prevention; Metabolic Diseases; Endocrinology